MUHAMMAD ABDUH: REFORMASI DAN PURIFIKASI INTELEKTUALITAS DUNIA PENDIDIKAN ISLAM TAHUN 1866-1905M - Budi Darmawan; Eka Putra Wirman; Zainal Zainal; Efendi Efendi (AL Fikrah: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Muhammad Abduh was a reformer and thinker who was very influential in the history of Islamic thought. His thoughts have had a significant impact on various stages of people's thinking life including aspects of Al-Qur'an interpretation, education, social, politics, civilization and so on. But the focus of the discussion in this article is about thinking and its contribution to education because education for Abduh is very important in determining the wheel of progress for future generations. Abduh's belief in the power of reason made Muhammad Abduh apply a lot of understanding which said that humans have freedom of thought and action according to the teachings he brought. Abduh reformed various sectors, but his biggest reform was through education. Abduh made education the main way to purify the Islamic world which was polluted by taklid. This education reform by Muhammad Abduh aimed to restore reason to a proper position in the Islamic world, because a reform and purification of education will have a long-lasting impact. and continuously on Muslims.